2007
DOI: 10.5194/acp-7-4065-2007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and modelling of the size fractionated aerosol particle number concentration measurements nearby a major road in Helsinki – Part I: Modelling results within the LIPIKA project

Abstract: Abstract.A field measurement campaign was conducted near a major road "Itäväylä" in an urban area in Helsinki in 17-20 February 2003. Aerosol measurements were conducted using a mobile laboratory "Sniffer" at various distances from the road, and at an urban background location. Measurements included particle size distribution in the size range of 7 nm-10 µm (aerodynamic diameter) by the Electrical Low Pressure Impactor (ELPI) and in the size range of 3-50 nm (mobility diameter) by Scanning Mobility Particle Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Limited primarily by instrument response time, many mobile monitoring campaigns to assess near-road spatial concentration gradients have been restricted to repeatedly stopping at preselected locations and collecting data for a short period of time. 2,4,[11][12][13] These studies have provided substantial information on near-road concentration gradients and demonstrated the capability of mobile monitoring to augment conventional stationary monitoring sites. However, all are limited to monitoring at only a few locations near the roadway of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Limited primarily by instrument response time, many mobile monitoring campaigns to assess near-road spatial concentration gradients have been restricted to repeatedly stopping at preselected locations and collecting data for a short period of time. 2,4,[11][12][13] These studies have provided substantial information on near-road concentration gradients and demonstrated the capability of mobile monitoring to augment conventional stationary monitoring sites. However, all are limited to monitoring at only a few locations near the roadway of interest.…”
Section: Discussionmentioning
confidence: 99%
“…They categorized the aerosol to several types: central European aerosol, Nordic aerosol, mountain sites, and southern and western European regions, and analysed the seasonal characteristics and patterns of the various size modes. Hussein et al (2007) and Pohjola et al (2007) conducted a field measurement campaign near a major road in an urban area in Helsinki in February 2003. Measured PNC data at various distances from the road was compared with dispersion and aerosol process model predictions.…”
Section: J Kukkonen Et Al: Modelling the Dispersion Of Particle Nummentioning
confidence: 99%
“…Gross and Baklanov, 2004;Dusek et al, 2006;Pohjola et al, 2007;Hussein et al, 2007;Medina et al, 2007;Langmann et al, 2008). The aerosol processes include the growth and nucleation processes, and the transport and deposition pathways of the aerosols.…”
Section: Improved Understanding and Parameterization Of Physical Procmentioning
confidence: 99%